Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1080/09168451.2017.1365592
|View full text |Cite
|
Sign up to set email alerts
|

Emodin extends lifespan of Caenorhabditis elegans through insulin/IGF-1 signaling pathway depending on DAF-16 and SIR-2.1

Abstract: The naturally occurring anthraquinone emodin has been serving primarily as an anti-bacterial and anti-inflammatory agent. However, little is known about its potential on anti-aging. This investigation examined the effect of emodin on lifespan and focused on its physiological molecular mechanisms in vivo. Using Caenorhabditis elegans (C. elegans) as an animal model, we found emodin could extend lifespan of worms and improve their antioxidant capacity. Our mechanistic studies revealed that emodin might function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…The IIS pathway is a highly conservative and elaborate lifetime regulator, which plays a key role in development, metabolism, and aging in C. elegans [3]. This signaling pathway is activated by the translocation of DAF-16 to the nucleus [34]. The upregulation of daf-16 was combined with the downregulation of age-1 and activation of downstream target antioxidant genes sod-3 and gst-4 to pave the way for post-transcriptional exploration in the IIS pathway in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The IIS pathway is a highly conservative and elaborate lifetime regulator, which plays a key role in development, metabolism, and aging in C. elegans [3]. This signaling pathway is activated by the translocation of DAF-16 to the nucleus [34]. The upregulation of daf-16 was combined with the downregulation of age-1 and activation of downstream target antioxidant genes sod-3 and gst-4 to pave the way for post-transcriptional exploration in the IIS pathway in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Single mutation of IIS genes such as daf-2, age-1, or daf-16 leads to inhibition of the IIS pathway and extension of lifespan (Uno and Nishida, 2016). In this review, most studies were found to be done on daf-2, daf-16, age-1, skn-1, hsf-1, and sir-2.1 genes, which are all 3 (Chaudhari and Kipreos, 2017) No data 20 • C Liquid E. coli OP50 (Zhao et al, 2017) 50 (Im et al, 2016) 40-50 (Bansal et al, 2015) 120 Table 2 continued 15 (Rathor et al, 2015) 80-100…”
Section: Resultsmentioning
confidence: 99%
“…Treatment with lowbush cranberry and essential oil alloaromadendrene failed to increase the lifespan of daf-16 mutants, indicating that a DAF-16/FOXO transcription factor is required but not Alaskan blueberry (Scerbak, Vayndorf, Hernandez, McGill, & Taylor, 2018;Yu et al, 2014). The protective effect of low-concentration arbutin against aging and oxidative stress was also dependent on DAF-16, indicating that arbutin-treated C. elegans exhibited increased resistance to stress (Zhou et al, 2017). Blueberry extract (BE) exerted no significant effect on the lifespan of daf-16 mutants, and the increased genetic expression level suggested that BE could promote daf-16 expression and then increase downstream sod-3 expression to extend lifespan and stress resistance (Wang, Liu, Li, & Liu, 2018).…”
Section: Daf-16mentioning
confidence: 98%